Standard soil methods for long-term ecological research - Robertson, G. P. (Long-Term Ecological Research Network series ;, 1999)
Standardized methods and measurements are crucial for ecological research, particularly in long-term ecological studies where the projects are by nature collaborative and where it can be difficult to distinguish signs of environmental change from the effects of differing methodologies. This second volume in the Long-Term Ecological Research (LTER) Network Series addresses these issues directly by providing a comprehensive standardized set of protocols for measuring soil properties. The goal of the volume is to facilitate cross-site synthesis and evaluation of ecosystem processes. Chapters cove.